Inhibition of food-spoilage and foodborne pathogenic bacteria by a nisin Z-producing Lactococcus lactis subsp. lactis KT2W2L. (1st September 2017) - Hwanhlem, Noraphat; Ivanova, Teodora; Haertlé, Thomas; Jaffrès, Emmanuel; Dousset, Xavier
Abstract: The growth of food-spoilage and foodborne pathogenic bacteria was inhibited by a nisin Z-producing Lactococcus lactis subsp. lactis KT2W2L as determined by the agar spot test and agar well diffusion assay. The growth of Brochothrix thermosphacta DSMZ 20171 T and Staphylococcus aureus CIP 76.25 was inhibited when co-cultivated with L. lactis subsp. lactis KT2W2L whereas the growth of Escherichia coli CIP 76.24 and Salmonella Enteritidis CIP 81.3 was not. However, the growth level of E. coli CIP 76.24 and S . Enteritidis CIP 81.3 co-cultivated with L. lactis subsp. lactis KT2W2L was diminished compared to cultivation without L. lactis subsp. lactis KT2W2L. The neutralized cell-free supernatant (NCFS) collected from the culture of L. lactis subsp. lactis KT2W2L, cultivated with and without indicator strain, exhibited inhibition zones against the indicator strains as determined by the agar well diffusion assay. The results reported in this study indicate that a nisin Z-producing L. lactis subsp. lactis KT2W2L may find application as a bio-preservative for reducing food-spoilage and foodborne pathogens in food products. Highlights: Lactococcus lactis subsp. lactis KT2W2L is a nisin Z producer. L. lactis subsp. lactis KT2W2L showed activities against food-spoilage organisms and foodborne pathogens. L. lactis subsp. lactis KT2W2L has the potential to be used as a bio-control agent.